Kepribadian dalam Perspektif Sigmund Freud dan Al-Qur’an : Studi Komparatif - Muhammad Irfan Helmy (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2018)
Human personality depicts an individual’s behavior and it is a formal object of psychology. Understanding human behavior is a vital and fundamental subject to understand human’s essence. The typology of behavioral concept is multifaceted and varied. In fact, various definitions of personality arrive at a single substance. This paper analyses Sigmund Freud’s concept on personality through the eye of Qur’an. The Qur’an made a personality concept as part of its focus. Through a comparative method, this study concludes that both Freud and the Qur’an argue that human personality consists of three components or potentials with different characteristics, yet integrated, to create human behavior and its personality. Freud calls them consecutively as Id, Ego and Superego; while the Quran calls them as Nafs, Akal and Kalbu. The difference between Freud and Quran on personality concept lies on the source where these three potentials came from. In Freud’s view, they came from the human being themselves internally or being influenced by their surroundings. Freud did not count God’s influence in his theory. According to Quran, however, the third potentials (Kalbu)depicts God’s values embedded in human being. Kalbu is called as a God’s disposition (tendency). Thus, Quranic concept on personality is theocentric while Freud’s is anthropocentric which is much dependent on rationality and morality of human being.